FLUOR PADA RESTORASI GLASS IONOMER CEMENT DAN RESIN KOMPOSIT TERHADAP PERUBAHAN pH - Ratnasari Diah P.; Lies Elina P. (Jurnal Kesehatan Gigi (Dental Health Journal), 2021)
Aesthetically, a consideration in carrying out dental caries restoration. material which is often used as a restoration material is glass ionomer cement and composite resin, this restoration material is tooth-colored, has good strength and both contains fluorine and gives a good aesthetic. The purpose of this study is to see the effectiveness of fluoride content in both of these materials against changes in salivary pH in preventing secondary caries. This type of experimental research with the design of one group pretest-posttest design, sampling using a simple random sampling technique. The location of the study was 32 students in the fifth grade SDN Rajabasa Jaya, Bandar Lampung. It was concluded that the restoration using glass ionomer cement overlay material was more significant in influencing changes in salivary pH compared to composite resin material overlay, the release of fluorine in glass ionomer cement restoration was highest on the 7th day after restoration, decreasing the next day.